Official batch control of influenza vaccines: Is it still useful?. Issue 17 (19th April 2018) - Kretzschmar, Evelyne; Muckenfuss, Heide; Pfleiderer, Michael
Highlights: Evaluation on the impact of governmental batch release for influenza vaccines in Europe. Notifications within the OCABR network from 2006–2016 were evaluated. OMCLs prevented 13 batches of insufficient quality from being administered. Governmental batch release system ensures quality and safety of influenza vaccines. Abstract: Introduction: The governmental quality control of human vaccines is a long established tradition in many European countries. In Germany, vaccines have been controlled by a governmental agency since 1935. In the beginning, vaccine production and control was a purely national activity. However, that changed fundamentally in 1994 when the so-called Official Control Authority Batch Release Network (OCABR) was implemented shortly after the establishment of the European Union. Today, Official Medicinal Control Laboratories (OMCLs) are part of the European OCABR Network. In many European countries, OMCLs experimentally test every batch of human vaccines before they enter the market. We wanted to gain insights into the benefits of batch release by the Network and address the question whether batch release is still useful. This question was investigated in the context of influenza vaccines. Methods: Notifications on influenza vaccines circulated from 2006 to 2016 within the OCABR network were compiled and organized into 32 cases. The impact of these findings was evaluated, and the communication pathways between companies and respective European control laboratories were examined. Results: Approximately 5850 batches were tested by the OMCL network between 2006 and 2016. Among these, notifications belonging to 32 cases were observed. The predominant proportion of the circulated notifications related to manufacturing issues. In most cases, the manufacturer itself had withdrawn the batches before they entered the market. However, in three cases, batches of insufficient quality were detected by the respective European Control Laboratory leading to withdrawal of 13 batches. Conclusion: 13 batches which did not meet the specifications of influenza vaccine were detected by the OMCL network between 2006 and 2016 which would not have been identified by the manufacturer. This demonstrates the impact of governmental batch release. Together with the intrinsic values of the OCABR system and keeping in mind that vaccines are given to healthy often young individuals, governmental batch release of influenza vaccines is still justified.